Responsibility of the heirs of personal guarantee holders in bankruptcy from Islamic inheritance law and state law: A case of Indonesia - Idham, Idham; Nadriana, Lenny; Febriansyah, Febriansyah (Jurnal Manajemen Strategi dan Aplikasi Bisnis, 2023)
The responsibility of heirs of personal guarantee holders in companies facing bankruptcy is a complex and significant issue in the legal world. In the business sphere, especially in the current era of globalization and intense competition, business transactions and agreements often involve different guarantees provided by the parties involved. Personal guarantees, which require an individual to secure a company's obligations or debts, are one form of security that is commonly used. When a company given a personal guarantee faces financial difficulties or goes bankrupt, the issue of how the heirs should handle the assets left by the heir with a personal guarantee becomes very relevant. Additionally, the responsibility of heirs in this context, as viewed by Islamic law, and how it relates to applicable civil law principles, is an important aspect that needs careful examination. This article aims to comprehensively explain the concept of heir responsibility from the heirs of personal guarantee holders in two legal frameworks, namely Islamic law and civil law. We will explore the legal aspects governing the responsibilities of heirs in both legal systems, highlight the differences and similarities between the two, and provide a clear understanding of the topic.